Meticillin-susceptible Staphylococcus aureus transmission among healthcare workers, patients and the environment in a large acute hospital under non-outbreak conditions investigated using whole-genome sequencing. (September 2022) - Kinnevey, P.M.; Kearney, A.; Shore, A.C.; Earls, M.R.; Brennan, G.I.; Poovelikunnel, T.T.; Humphreys, H.; Coleman, D.C.
Summary: Background: The role of meticillin-susceptible Staphylococcus aureus (MSSA) colonization of healthcare workers (HCWs), patients and the hospital environment in MSSA transmission events (TEs) is poorly understood. Aims: The role of meticillin-resistant Staphylococcus aureus (MRSA) was investigated recently under non-outbreak conditions in a large hospital with a history of endemic MRSA over 2 years using whole-genome sequencing (WGS). Numerous potential MRSA TEs were identified. The present study investigated MSSA TEs from the same sources during the same 2-year hospital study. Methods: HCW ( N =326) and patient ( N =388) volunteers on nine wards were tested for nasal and oral MSSA colonization over 2 years. Near-patient environment ( N =1164), high-frequency touch sites ( N =810) and air ( N =445) samples were screened for MSSA. Representative MSSA and clinical isolates were sequenced and analysed by core genome multi-locus sequence typing. Closely related isolates (≤24 allelic differences) were segregated into related isolate groups (RIGs). Potential TEs involving MSSA in RIGs from HCWs, patients and patient infections were identified in combination with epidemiological data. Findings: In total, 635 MSSA were recovered: clinical isolates ( N =82), HCWs ( N =170), patients ( N =120), and environmental isolates ( N =263). Twenty-four clonal complexes (CCs) were identified among 406/635 MSSA sequenced, of which 183/406 segregated into 59 RIGs. Numerous potential HCW-to-patient, HCW-to-HCW and patient-to-patient TEs were identified, predominantly among CC5-MSSA, CC30-MSSA and CC45-MSSA. HCW, patient, clinical and environmental isolates were identified in 33, 24, six and 32 RIGs, respectively, with 19/32 of these containing MSSA related to HCW and/or patient isolates. Conclusions: WGS detected numerous potential hospital MSSA TEs involving HCWs, patients and environmental contamination under non-outbreak conditions.